A Study on Clinical Features and Cost Incurred by Dengue Syndrome Patients Admitted to A Tertiary Care Hospital - Sathish Chandra MR; Ashwath Narayana DH; Manjunath M (Medsci Publications, 2014)
Introduction: Dengue infections are a significant cause of morbidity and mortality which leads to adverse economic effects in many developing tropical countries. The present study allows in better understanding of the clinical presentations and also helps in describing economic burden of the same. Objective of the study wasto describe the clinical features, case fatility and cost incurred of dengue syndrome admitted to tertiary care hospital. Methodology:It was descriptive study done on patients admitted with clinical signs and symptoms of dengue during 2010-11 at KIMS Hospital & Research Center, Bangalore. The cost incurred by the patients in respect to hospital charges, laboratory investigations and drugs provided will be analyzed from the entries from the case records. These patients will be followed up through telephone contact provided in the case records. Results: Out of 325 cases who had clinical signs and symptoms of dengue, 200 were found positive NS1 Ag/IgM/IgG for dengue. 62% among them were males. 35.5% were in the age group of 21-30 years. Majority (92.5%) had Classical Dengue followed by DHF (7%) and DSS (0.5%). Most common clinical symptom was fever (94%) followed by vomiting (45.5%) and abdominal pain (33%). Hemoglobin was >12gm% in 73.4% of cases. Case fatality was found to be 1.5%. Direct median cost was found to be Rs.12,611/- and indirect median cost was Rs.3109/- Conclusion: Professionals and public should be made aware of common clinical manifestations of dengue syndrome for early reporting and seeking prompt treatment there by reducing the case fatality rate and the economic loss to the patients and country at large.